Bacteraemia in neonatal foals: clinicopathological differences between Gram-positive and Gram-negative infections, and single organism and mixed infections - Corley, K.T.T; Pearce, G; Magdesian, K.G; Wilson, W.D (Equine veterinary journal, 2007)
Treatment for bacteraemia in foals must be started before the identity of the causative organism is known. Information aiding selection of effective antimicrobials should improve outcome. To describe differences in clinical and clinicopathological data and outcome in foals with bacteraemia due to different classes of bacteria. Records of foals with a positive blood culture, age < 10 days and presenting to a university hospital 1995-2004, were reviewed. Bacterial culture results, subject details, historical information, physical examination findings at admission and clinicopathological data generated during the first 48 h of hospitalisation were analysed. Results from foals with Gram-positive or Gram-negative organisms, single or mixed organism bacteraemias, and with bacteraemia due to 3 commonly isolated organisms were compared. Eighty-five foals met the inclusion criteria. Gram-negative organisms (n = 59) Gram-positive organisms (n = 13) or multiple organisms (n = 19) were cultured from individual foals. Foals with Gram-negative bacteraemia had lower total white blood cell and lymphocyte counts at admission than did those from which only Gram-positive bacteria were cultured. Mixed organism bacteraemia was associated with tachycardia, increased serum concentrations of sodium, chloride and urea nitrogen, acidosis, respiratory distress, recumbency on admission and nonsurvival. Actinobacillus spp. infections were associated with leucopenia, neutropenia, lymphopenia and depression on hospital admission. Recognising particular patterns of clinical and clinicopathological findings associated with infection with specific groups of bacteria may, in the future, aid antimicrobial selection and influence prognosis in bacteraemic foals.